Experimental investigation of the thermal performance of an air-to-air horizontal heat pipe heat exchanger - Yau, Yat Huang; Ahmadzadehtalatapeh, M. (SpringerOpen, 2010)
An experimental study has been performed to investigate the thermal performance of a 2-row copper-R134a horizontal heat pipe heat exchanger in different working conditions. During the tests, dry bulb temperature of evaporator inlet has been controlled at 27-35°C while the condenser inlet dry bulb temperature was kept constant at about 24 °C . The influence of face velocity on the performance of heat pipe heat exchanger was also studied. The thermal resistance of the single heat pipe identical to the heat pipes embedded in the heat pipe heat exchanger was estimated using the recommended mathematical correlations and compared to the experimental results. The investigation has been carried out for 30 experiments and the results are presented in the present paper.